A dominant-negative form of Serrate acts as a general antagonist of Notch activation. - Hukriede, N.A.; Gu, Y.; Fleming, R.J. (Development, 1997)
Specification of the dorsal-ventral compartment boundary in the developing Drosophila wing disc requires activation of NOTCH from its dorsal ligand SERRATE and its ventral ligand DELTA. Both NOTCH ligands are required in this process and one cannot be substituted for the other. In the wing disc, expression of a dominant-negative, truncated form of SERRATE called BD(G), is capable of inhibiting NOTCH activation in the ventral but not the dorsal compartments. We demonstrate that BD(G) can act as a general antagonist of both SERRATE and DELTA mediated NOTCH interactions, however, BD(G) retains the SERRATE protein domain targeted by FRINGE, hence its antagonistic effects are restricted in the dorsal wing disc. Our findings suggest a model in which ligand binding to NOTCH is a necessary but insufficient step toward NOTCH activation.